Identification and distribution of hard tick species in Waglasta, Amhara, Ethiopia: modeling of local habitat suitability of dominant species - Assefa, Ayalew; Tibebu, A. (Springer, 2026)
Ethiopia ranks first in Africa and tenth globally in livestock population. However, this resource contributes only minimally to the national economy, with ticks and tick-borne diseases posing major constraints. A cross-sectional study was conducted from April 2020 to June 2021 to identify the prevalent ticks and delineate suitability of the local habitants for spatial distribution of dominant tick species in the Wag-Lasta area, Ethiopia. The tick infestation data were collected from georeferenced sampling sites, ticks were identified based on morphological characteristics, and bioclimatic variables were obtained from the WorldClim 2.1 database. The results identified three tick genera: Rhipicephalus (52.5%), Amblyomma (40.7%), and Hyalomma (6.9%), and nine species: A. variegatum, R. pravus, R. decoloratus, A. cohaerens, R. evertsi, H. truncatum, R. pulchellus, H. rufipes, and H. marginatum. The male-to-female and adult-to-nymph tick stage ratios were 1:1 and 1.6, respectively. A. variegatum dominated the highlands and midlands, and R. pravus was more prevalent in the lowlands. Annual temperature range was the main contributor variable for A. variegatum (32.6%) and R. pravus (27%), followed by precipitation during the warmest and wettest quarters, isothermality, and precipitation seasonality. The ensemble models mapped the distribution of the two most abundant tick species with excellent predictive performance for A. variegatum (TSS = 0.94, ROC = 0.99) and for R. pravus (TSS = 0.94, ROC = 0.99). In conclusion, A. variegatum and R. pravus were the predominant tick species with distinct ecological distribution across agroecology, mainly influenced by the annual temperature range and precipitation-related bioclimatic factors.